2013
DOI: 10.1097/wno.0b013e318267fd5f
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness in Patients With Alzheimer Disease

Abstract: The aim of this study was to investigate retinal nerve fiber layer (RNFL) thickness in patients with Alzheimer disease (AD) without visual impairment using spectral domain optical coherence tomography (SD-OCT) and to compare the results with healthy controls. A total of 80 subjects, including 40 patients with early untreated AD (mean age, 69.3 ± 4.9 years) and 40 healthy controls (mean age, 68.9 ± 5.1 years) were enrolled. Both eyes of patients with AD and controls were imaged using SD-OCT. The average RNFL th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
139
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 13 publications
12
139
1
2
Order By: Relevance
“…This is consistent with previous OCT findings 13, 15, 16, 17, 18, 20. The preferential loss of fibers in the superior quadrant is also compatible with the predominant inferior visual field defect documented in AD patients 56.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous OCT findings 13, 15, 16, 17, 18, 20. The preferential loss of fibers in the superior quadrant is also compatible with the predominant inferior visual field defect documented in AD patients 56.…”
Section: Discussionsupporting
confidence: 92%
“…In vivo studies with optical coherence tomography (OCT) corroborated these findings, showing a reduction of the retinal nerve fiber layer (RNFL) thickness in AD patients 12, 13, 14, 15, 16, 17, 18, 19, 20. Accumulation of Aβ in the retina of AD patients has also been reported in a few studies.…”
mentioning
confidence: 60%
“…No statistically significant differences in GC-IPL thickness between AD and MCI most affected. While some studies report preferential superior quadrant RNFL thinning in AD, which would explain the predominantly inferior visual field defects previously described in AD [40,45,47,54,[70][71][72], other authors have reported different findings; these results are presented in Table 1. A meta-analysis of TD-OCT studies in AD demonstrated that peripapillary RNFL thinning occurred in all retinal quadrants [73].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 91%
“…A meta-analysis of TD-OCT studies in AD demonstrated that peripapillary RNFL thinning occurred in all retinal quadrants [73]. However, more recent SD-OCT studies have reported different findings, with most SD-OCT studies suggesting selective superior RNFL thinning [39,54,70]. Two more recent meta-analyses, which used both TD-OCT and SD-OCT studies, aimed to determine the diagnostic utility of OCT measurements of RNFL thickness in AD [74,75].…”
Section: Pathological Changes In the Retina And Optic Nervementioning
confidence: 99%
“…Recent studies have revealed degenerative changes in optic nerve fibers, causing thinning of the retinal nerve fiber layer (RNFL) in patients with AD (Berisha et al 2007; Kirbas et al 2013). The RNFL comprises axons originating in retinal ganglion cells and can be measured using ocular imaging technologies such as optical coherence tomography (OCT), which provides non-invasive, rapid, objective and reproducible measurements.…”
mentioning
confidence: 99%